Curriculum management of the Reading Promotion Policy at Escuela Unificada República de Perú - Arias Gamboa, Jacqueline (2024)
This paper aims to examine the curricular management undertaken by the principal at Escuela Unificada República de Perú for the implementation of the Reading Promotion Policy. It is of interest to educational administration because the effective integration and coordination of this policy into the school curriculum contribute to the improvement of educational quality. This is because, by establishing a meaningful correlation between policies and curriculum planning, educational administration can optimize available resources and cultivate an environment that strives for quality and excellence in the teaching-learning process. This study employs a qualitative research approach with a phenomenological design, allowing us to comprehend the study phenomenon through the experiences and perspectives of the informants. To collect information, non-participant observation, semi-structured interviews, and focus groups are implemented as research techniques. Twelve informants, distributed among the teaching, administrative, and administrative technical staff, are part of the sample. The findings reveal a significant factor: the lack of family support, which is crucial for the initial development of reading and writing skills. The school lacks an Institutional Reading Plan (PIL), and there is also a deficiency in training for the teaching and administrative staff regarding the Reading Promotion Policy. This implies that there is no curricular management process that allows the integration of said policy into the school curriculum.